Exposure of neonatal female rats to bisphenol A disrupts hypothalamic LHRH pre-mRNA processing and estrogen receptor alpha expression in nuclei controlling estrous cyclicity - Monje, Lucas Daniel (2010)
This study examines the effects of neonatal exposure to the endocrine disruptor bisphenol A (BPA) on the neural network that controls estrous cyclicity. From postnatal day 1 (PND1) to PND7, female pups were injected with vehicle (control) or BPA (BPA.05: 0.05. mg/kg-d, BPA20: 20. mg/kg-d). At PND100 BPA.05-females showed alterations in estrous cyclicity and BPA20-females were incapable of producing an estradiol-induced LH surge. By real-time PCR we determined that hypothalamic expression of mature LH-releasing hormone (LHRH) mRNA was increased in BPA.05 and decreased in BPA20-females. Furthermore, unprocessed intron A-containing LHRH RNA was decreased in the cytoplasm of hypothalamic cells of both groups. Immunohistochemistry revealed that estrogen receptor alpha protein was up-regulated in anteroventral periventricular and down-regulated in arcuate nucleus of both groups. Our results show that BPA permanently disrupts hypothalamic LHRH pre-mRNA processing and steroid receptors expression in nuclei that control estrous cyclicity in adult rats.